Influence of air Gap Between the Transformer of Resistance and Object of Monitoring on Temperature Measurement Error; European Physical Journal Web of Conferences (EPJ Web of Conferences); Vol. 110 : Thermophysical Basis of Energy Technologies - Atroshenko Yu. K. Yuliana Konstantinovna (2016, 2016)
Title screen